How are Portuguese Public Libraries "facing" Covid-19 - Alvim, Luísa; Silva, Ana Margarida Dias da; Borges, Leonor Calvão (Qualitative and Quantitative Methods in Libraries, 2021)
Between March, 18 th and May 2 nd 2020, Portuguese public libraries were forced to lockdown, like the rest of the country, because of the declaration of the emergency period by the Portuguese government due to Covid19 pandemia. Away from public facing traditional services, Portuguese public libraries had to adapt to new pandemic reality. This paper aims to analyse what were the challenges and the strategies adopted by Portuguese public libraries, namely using Facebook, from a sample of 18 libraries, one of each Portuguese district. Also, we can concluded that the National Public Libraries Network (RNBP), coordinated by the Directorate-General for Books, Archives and Libraries (DGLAB), was of great importance on encouraging and engaging online initiatives.